Validation of the Turkish version of the Celiac Disease Questionnaire (CDQ) - Aksan, Aysegul; Mercanligil, Seyit Mehmet; Hauser, Winfried; Karaismailoglu, Eda (Bmc, 2015)
Introduction: The aim of the study was to translate, adapt and validate the Celiac Disease Questionnaire (CDQ), which was developed in Germany, for use in Turkey. Methods: The questionnaire was translated by a forward-backward translation method. Total CDQ score and four subscores (emotional state, gastrointestinal symptoms, worries, social problems) were calculated and their reliability assessed by internal consistency. Reliability of scales was evaluated by internal consistency. Test-retest reliability was assessed by means of a retest after 15 days. Face validity was assessed by patient volunteers and physicians and construct validity was assessed by means of confirmatory factor analysis. Convergent validity was determined by comparing responses to the CDQ with similar subscale scores of the Short Form-36 (SF-36) health survey. Discriminative concurrent criterion validity was determined by comparing the CDQ scores of patients with celiac disease (CD) on a gluten-free diet (GFD) with CD patients not on a GFD. Results: The Turkish version of the CDQ was completed by 205 patients with celiac disease (Female 146, mean age 31.1 year, +/- 10.61). The Cronbach-alpha coefficent of the subscores ranged between 0.73 and 0.93. Test-retest reliability was 0.99 for all subscores. 42 patients with CD and five gastroenterologists assessed the items of the CDQ to be comprehensible and relevant to the health related quality of life (HRQOL) of CD patients. The confirmatory factor analysis demonstrated acceptable fit indices for the original four subscales of the CDQ. The correlations between the scales of the CDQ and the instrument for validation covering similar dimensions of the HRQOL ranged between 0.61 and 0.93. In all subscores and in the total score, patients not on a GFD showed a significantly reduced HRQOL (all p < 0.05) compared to patients on a GFD. Conclusion: The Turkish version of the CDQ proved to be a reliable and valid instrument for measuring HRQOL in Turkish patients with celiac disease.
Keywords: Celiac disease; Health related quality of life; Celiac Disease Questionnaire CDQ; Validation; Turkey